Don Q, son of Zorro - Crisp, Donald, 1880-1974; Cunningham, Jack, 1882-1941; Fairbanks, Douglas, 1883-1939; Astor, Mary, 1906-1987; Prichard, K. (Kate).; Hesketh-Prichard, H. (Hesketh), 1876-1922.; Elton Corporation; Cinetel Films ([Los Angeles, CA] : Elton Corporation, 1925)
In this sequel to the Mark of Zorro (1920) Fairbanks plays the whip wielding Don Q, son of the famous California Zorro, who continues the fight for justice as a student in Spain.
Originally produced as silent motion picture in 1925.
Based on: Don Q's love story / K. and Hesketh Prichard.
Douglas Fairbanks, Mary Astor, Jack McDonald, Donald Crisp, Stella DeLanti, Warner Oland, Jean Hersholt.
Cinematographer, Henry Sharp; editor, William Nolan; music, Mortimer Wilson.
Silent film with English intertitles and musical background.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed January 8, 2016).
Keywords: Zorro (Fictitious character); Silent films; Film adaptations; Swashbuckler films; Western films; Feature films; Action and adventure films; Internet videos; Streaming video